Antiplatelet efficacy of ticagrelor versus clopidogrel in Mediterranean patients with diabetes mellitus and chronic coronary syndromes: A crossover pharmacodynamic investigation - Ana Lucrecia Marcano; Ana Lucrecia Marcano; Montserrat Gracida; Montserrat Gracida; Gerard Roura; Gerard Roura; Josep Gomez-Lara; Josep Gomez-Lara; Rafael Romaguera; Rafael Romaguera; Luis Teruel; Luis Teruel; et al. (Frontiers in Cardiovascular Medicine, 2022)
IntroductionPatients with diabetes mellitus (DM) have augmented platelet reactivity and diminished responsiveness to clopidogrel. Ticagrelor, a more potent P2Y12 inhibitor, is clinically superior to clopidogrel in acute coronary syndromes, although its role in chronic coronary syndromes (CCS) is still the subject of debate. The aim of this investigation was to compare the pharmacodynamic effectiveness of ticagrelor and clopidogrel in Mediterranean DM patients with CCS.Materials and methodsIn this prospective, randomized, crossover study, patients (n = 20) were randomized (1:1) to receive, on top of aspirin therapy, either ticagrelor 180 mg loading dose (LD)/90 mg maintenance dose (MD) b.i.d. or clopidogrel 600 mg LD/75 mg MD o.d. for 1 week in a crossover fashion with a 2–4 week washout period between regimens. Platelet function measurements were performed at 4 timepoints in each period (baseline, 2 h and 24 h after LD, and 1 week), including light transmission aggregometry (LTA, primary endpoint), VASP assay, Multiplate and VerifyNow P2Y12.ResultsThe ticagrelor LD achieved greater platelet inhibitory effect than clopidogrel LD, assessed with LTA (20 μM ADP as agonist), at 2 h (34.9 ± 3.9% vs. 63.6 ± 3.9%; p < 0.001) and 24 h (39.4 ± 3.5% vs. 52.3 ± 3.8%; p = 0.014). After 1 week of therapy, platelet reactivity was again significantly inferior with ticagrelor compared to clopidogrel (30.7 ± 3.0% vs. 54.3 ± 3.0%; p < 0.001). The results were consistent with the other platelet function assays employed.ConclusionIn Mediterranean patients with DM and CCS, ticagrelor provides a more potent antiplatelet effect than clopidogrel after the LD and during the maintenance phase of therapy.Clinical trial registration[ClinicalTrials.gov], identifier [NCT02457130].